2023
DOI: 10.1007/s12011-023-03838-2
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Cadmium, and Arsenic in Raw Milk Produced in the Vicinity of a Mini Mineral Concentrator in the Central Andes and Health Risk

Doris Chirinos-Peinado,
Jorge Castro-Bedriñana,
Elva Ríos-Ríos
et al.

Abstract: The bovine milk quality, safety, and security are of great concern mainly due to the dispersion of toxic substances from various anthropogenic activities and poor practices for organophosphates in agriculture use. This study evaluated the potential risk to human health from lead (Pb), cadmium (Cd), and arsenic (As) from the consumption of milk produced in an area of the Central Andes valley near a mini mineral concentrator by estimating the weekly intake (WI), dietary risk quotient (DRC), hazard quotient (THQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…In these five studies, As levels are in the safe range and were not reported beyond the local standard limits of the studied countries and EU and FAO/WHO standards. Although the number studies related to measuring As in pasteurized and sterilized milk across the world was so limited; several studies evaluated As concentration in raw cow’s milk which report higher values than ours from Córdoba, Argentina with mean concentration between 0.0003 and 0.0105 mg/kg [ 8 ]; in Iran, in the range of 0.015 to 0.026 mg/kg [ 89 ], in Alabria, Italy, reporting an average As content of 0.038 mg/kg of raw milk, in Slovakia, with mean concentration of As < 0.03 mg/kg [ 8 , 10 ]. All these low concentrations of As in raw cow’s milk and pasteurized and sterilized milk are indicative that As use in the transformation of dairy products is safe for consumer and it does not pose health risks for human consumption.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…In these five studies, As levels are in the safe range and were not reported beyond the local standard limits of the studied countries and EU and FAO/WHO standards. Although the number studies related to measuring As in pasteurized and sterilized milk across the world was so limited; several studies evaluated As concentration in raw cow’s milk which report higher values than ours from Córdoba, Argentina with mean concentration between 0.0003 and 0.0105 mg/kg [ 8 ]; in Iran, in the range of 0.015 to 0.026 mg/kg [ 89 ], in Alabria, Italy, reporting an average As content of 0.038 mg/kg of raw milk, in Slovakia, with mean concentration of As < 0.03 mg/kg [ 8 , 10 ]. All these low concentrations of As in raw cow’s milk and pasteurized and sterilized milk are indicative that As use in the transformation of dairy products is safe for consumer and it does not pose health risks for human consumption.…”
Section: Resultsmentioning
confidence: 65%
“…It was also evidenced that Cd generally comes from phosphate fertilizers that contain up to 53.2 mg/kg of Cd [ 9 ]. Besides, equipment used in the production and packaging process is the likely other source of contamination [ 8 , 10 ]. The contamination of containers and equipment used in milking and pasteurization processes and environmental contamination were accounted to be among the factors affecting the elevated Cd concentration in the collected milk samples in their study [ 8 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grass samples were washed with tap water to remove soil particles, rinsed with deionized water [41], dried at 70 • C, and finely ground. The digestion and quantification of heavy metals in vegetative materials was the same as for soils samples and as described in earlier studies [42].…”
Section: Sample Preparation and Metal Analysismentioning
confidence: 99%
“…40 paper, and stored in polypropylene tubes under refrigeration. The procedure followed is detailed in Chirinos et al [42]. The Pb and Cd quantification was carried out in a flame atomic absorption spectrometer (NAMBEI AA320N) following the AOAC 973.35 method, using wavelengths of 283.3 and 228.8 nm for Pb and Cd, respectively [43,44].…”
Section: Sample Preparation and Metal Analysismentioning
confidence: 99%